The expression of miR-513c and miR-3163 was downregulated in tumor tissues compared with normal adjacent tissue of patients with breast cancer - Soheila Delgir; Khandan Ilkhani; Asma Safi; Yazdan Rahmati; Vahid Montazari; Zahra Zaynali-Khasraghi; Farhad Seif; Milad Bastami; Mohammad Reza Alivand (BMC, 2021)
Abstract Background Breast cancer (BC) is the most invasive cancer with different subtypes that its metabolism is unique compared with normal cells. Glutamine is considered critical nutrition that many cancer cells, particularly BC cells, are dependent on it for growth and proliferation. Therefore, targeting glutamine metabolism, especially enzymes that are related to this pathway, can be beneficial to design anti-cancer agents. Recent evidence has shown that microRNAs (miRNAs), with a short length and single-strand properties, play a prominent role in regulating the genes related to glutamine metabolism, which may control the development of cancer. Methods In silico analysis confirmed that miR-513c and miR-3163 might be involved in glutamine metabolism. The expression level of these two miRNAs was evaluated in eighty BC tissues and normal adjacent tissues. Furthermore, GSE38167, GSE38867, GSE42128, GSE45666, and GSE53179 were employed from gene expression omnibus (GEO). The Limma package was utilized to identify differentially expressed miRNAs (DEMs) of mentioned datasets to evaluate miR-513c and miR-3163 expression. Further, in silico analysis was utilized to predict the potential biological processes and molecular pathways of miR-513c and miR-3163, based on their target genes. Results In silico studies revealed top categories of biological processes and cellular pathways that might play a critical role in metabolism reprogramming and cancer development and were target genes for miR-513c and miR-3163. The current study showed that miR-513c (p value = 0.02062 and FC =  − 2.3801) and miR-3163 (p value = 0.02034 and FC =  − 2.3792) were downregulated in tumor tissues compared to normal adjacent tissues. The analysis of GEO microarray datasets showed that miR-513c was downregulated in GSE38167, GSE38867, GSE42128, GSE45666 and GSE53179, whereas there was a significant downregulation of miR-3163 in only two studies, including GSE38867 and GSE42128 that they were in accordance with our experimental results. Furthermore, the subgroup analysis did not show any substantial relationship between expression levels of these two miRNAs and factors such as age, family history of cancer, and abortion history. Conclusion MiR-513c and miR-3163 were downregulated in BC tissues, which might serve as tumor suppressors. They are suggested as potential therapeutic targets for patients with BC.